Thermoelastic properties of solids based on equation of state (International Journal of Mathematics and Physics, 2019)
Thermoelastic properties of solids at high pressures are studied using various equations of state (EOS) such as Eularian Birch-Murnaghan EOS, Poirier-Tarantola logarithmic EOS and the generalized Vinet-Rydberg EOS. We have determined the pressure derivatives of bulk modulus upto third order which are useful for predicting the Grüneisen parameter and its volume derivatives. Expressions have been obtained for the derivative properties based on different equations of state, and extrapolated to the limit of extreme compression. It is found that all the three equations lead to a common relationship between second and third pressure derivatives of bulk modulus in the limit of extreme compression.